Detection of ALK fusion variants by RNA-based NGS and clinical outcome correlation in NSCLC patients treated with ALK-TKI sequences. (October 2022) - Tabbò, Fabrizio; Muscarella, Lucia Anna; Gobbini, Elisa; Trombetta, Domenico; Castellana, Stefano; Rigutto, Angelica; Galetta, Domenico; Maiello, Evaristo; Martelli, Olga; Tiseo, Marcello; Scotti, Vieri; Ghilardi, Laura; et al.
Abstract: Introduction: Anaplastic lymphoma kinase (ALK) fusions identify a limited subset of non–small cell lung cancer (NSCLC) patients, whose therapeutic approach have been radically changed in recent years. However, diagnostic procedures and clinical-radiological responses to specific targeted therapies remain heterogeneous and intrinsically resistant or poor responder patients exist. Methods: A total of 290 patients with advanced NSCLC defined as ALK+ by immunohistochemistry (IHC) and/or fluorescent in situ hybridisation (FISH) test and treated with single or sequential multiple ALK inhibitors (ALKi) from 2011 to 2017 have been retrospectively retrieved from a multicentre Italian cancer network database. In 55 patients with enough leftover tumour tissue, specimens were analysed with both targeted and customised next generation sequencing panels. Identified fusion variants have been correlated with clinical outcomes. Results: Of the 55 patients, 24 received crizotinib as first-line therapy, 1 received ceritinib, while 30 received chemotherapy. Most of the patients (64%) received ALKi in sequence. An ALK fusion variant was identified in 73% of the cases, being V3 variant (E6A20) the most frequent, followed by V1 (E13A20) and more rare ones (e.g. E6A19). In three specimens, four new EML4-ALK fusion breakpoints have been reported. Neither fusion variants nor brain metastases were significantly associated with overall survival (OS), while it was predictably longer in patients receiving a sequence of ALKi. The presence of V1 variant was associated with progression-free survival (PFS) improvement when crizotinib was used ( p = 0.0073), while it did not affect cumulative PFS to multiple ALKi. Conclusion: Outcomes to sequential ALKi administration were not influenced by fusion variants. Nevertheless, in V1+ patients a prolonged clinical benefit was observed. Fusion variant identification by NGS technology may add relevant information about rare chromosomal events that could be potentially correlated to worse outcomes. Highlights: NGS platforms add relevant information to refine diagnosis of ALK+ NSCLC patients. RNA-based technologies allow the identification of rare/unknown EML4-ALK fusions. Fusion variants correlate with clinical outcomes to single/sequential ALKi. Molecular stratification of ALK+ patients may inform clinical strategies.